FAKTOR PENENTU PADA NIAT WARGA RUMAH TANGGA TERHADAP SURYA PANEL ATAP DI BANDUNG - Yosantia Bella (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
At the moment, Indonesia is developing and implementing renewable energy. This can be seen from the establishment of several new renewable energy generator programs in Indonesia, such as the geothermal power plant program in Garut and the floating solar power plant in Purwakarta. The Indonesian government has pledged to achieve a 23% renewable energy generation group by 2025. To make this possible, all parties, including the government, business actors, and the community, must cooperate. As a result, the purpose of this research is to identify the factors that influence household consumers' intentions to use rooftop solar panels in Bandung. This study employed a questionnaire method that was distributed online in order to collect data from 132 participants. Findings of this case study, by using TPB as a conceptual framework, it has been able to explain the determinant factors of the intentions of households in Bandung. Informative advertisements and reviews from trusted public figures/influencers can increase the intention of households to use rooftop solar panels.